Behavioral contrast without response-rate reduction - Halliday, M. S. (1974)
Behavioral contrast was obtained in two experiments, which both employed a standard free-operant successive discrimination (a multiple variable-interval extinction schedule), without the occurrence of reductions of response rate in the extinction component. In Experiment I, one group of four pigeons was trained on a multiple schedule in which one stimulus was associated with a variable-interval schedule and the second stimulus with response-independent reinforcement on a free variable-interval schedule. Though by the end of this training three pigeons were responding very little to the second stimulus, when this stimulus was associated with extinction all subjects showed a contrast effect. In Experiment II, eight pigeons were trained extensively to respond to a single stimulus on a variable-interval schedule, before a second stimulus associated with extinction was introduced. This second stimulus was dissimilar to the initial stimulus and five pigeons never responded in its presence. Nevertheless, all pigeons showed a contrast effect and there was no evidence that the effect was smaller in errorless subjects or smaller than in a subsequent discrimination where all subjects made many errors. Both experiments indicated that response reduction in one component of a multiple schedule is not a necessary condition for the occurrence of contrast.